Perception on ethical climate and individual job performance of bank employees - Hoàng, H?i Y?n (University of Economics Ho Chi Minh City, 2023)
This study investigates the impacts of various organizational ethical climates (egoism, principle, benevolence) on individual performance of bank employees. The research is conducted on the sample consisting of employees working in the commercial banks with less than 50% of state capital in Vietnam. The total of 364 valid complete questionnaires are input into SPSS database for processing. The research model and hypotheses are tested using the technique of Structural Equation Modeling. The research results show that different perceptions on organization ethical environment would lead to different individual performance. When the employee perceives his/her ethical environment as Eegoism, productivity, quality, and work efficiency would be significantly higher than those of the environments of benevolence. No impact, however, is identified of principle ethical environment on employees’ performance.